2018
DOI: 10.1161/hypertensionaha.118.11463
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Inflammatory Markers and Myocardial Fibrosis

Abstract: Inflammation promotes adverse ventricular remodeling. T1 mapping has been used to non-invasively assess interstitial myocardial fibrosis. We examined the association of baseline markers of systemic inflammation with interstitial myocardial fibrosis measured by extracellular volume fraction and native T1 mapping at 10 years’ follow-up in the Multi-Ethnic Study of Atherosclerosis. 772 participants had complete baseline data and underwent cardiac magnetic resonance imaging. All analyses were stratified by sex. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 35 publications
1
32
1
Order By: Relevance
“…Inflammation is found to be involved in the development and perpetuation of AF and AF-related thrombosis [ 23 ]. It also participates in the process of cardiac remodeling that leads to interstitial myocardial fibrosis [ 25 ]. The inflammation biomarker of CRP is found to be elevated in AF patients without coexistent cardiovascular disease [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation is found to be involved in the development and perpetuation of AF and AF-related thrombosis [ 23 ]. It also participates in the process of cardiac remodeling that leads to interstitial myocardial fibrosis [ 25 ]. The inflammation biomarker of CRP is found to be elevated in AF patients without coexistent cardiovascular disease [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between CRP and myocardial strain indices are reported in many cardiovascular diseases [ 27 30 ], and systemic inflammation is found to be linked to the impairment of myocardial contractility [ 29 ]. CRP is also reported to be associated with LV T1 mapping indices in patients with systemic inflammation involving the heart or general population without known cardiovascular disease [ 25 , 31 ]. The present study found a significantly elevated CRP in the AF patients (Table 2 ), and significant associations between the CRP and all five CMR-measured parameters of LAV, three LV circumferential strain indices and LV native T1 (Table 4 ), showing that at the early stage of AF inflammation might play a role in impairing morphology and function of both LA and LV in the paroxysmal AF patients with no coexistent cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial infarction (MI), commonly known as heart attack, is caused by the coronary artery lesions due to insufficient supply of oxygen (also known as ischemia); generally observed in old aged patients of more than 65 years [20]. Limited research studies have demonstrated an association of inflammatory markers with MI [21].…”
Section: Discussionmentioning
confidence: 99%
“…The link between myocardial inflammation and diffuse myocardial fibrosis is well-known [ 171 ]. Diffuse myocardial fibrosis may lead to left ventricular dysfunction and heart failure [ 172 ].…”
Section: Chest Imagingmentioning
confidence: 99%